Peningkatan Kualitas Sumber Daya Manusia sebagai Investasi Strategis melalui Peran Lembaga Pendidikan, Pemerintah, dan Widyaiswara - Desta Janu Kuncoro (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Enhancing human resource (HR) quality is a strategic priority for strengthening national competitiveness amid global dynamics and rapid digital transformation. This effort requires an integrated contribution from educational institutions, government agencies, and widyaiswara as key pillars in the national education and training system. This study aims to analyze the strategic roles of educational institutions, government agencies, and widyaiswara in enhancing human resource (HR) quality as a long-term investment within the national education system. The primary focus is to identify role disparities, assess institutional synergy, and formulate collaborative strategies for holistic, adaptive, and sustainable HR competency development. This research employs a systematic review approach following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. A total of 27 selected scientific articles out of 400 initial publications were analyzed through literature screening, inclusion–exclusion filtering, data extraction, and thematic analysis to gain a comprehensive understanding of HR investment through education and training. The findings reveal that educational institutions play a vital role in producing high-quality human resources through relevant curricula and competency-based learning innovation. The government supports this process through strategic policies, civil service capacity development, and institutional strengthening of training programs. Meanwhile, widyaiswara act as agents of change who bridge theory and practice in continuous professional development. The synergy among these three elements forms a critical foundation for building professional, competitive, and globally competent human resources in the era of digital transformation.